JPE Turnaround Times (Journal of Political Economy, 2022)
Previous articleNext article FreeJPE Turnaround TimesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreSummary Statistics of Turnaround Times, Current JPE EditorsOutcome of 1st Round DecisionsDays to DecisionMeanMedianDesk Rejection55%76Reject with Reviews40%9282Revise5%125111View Table Image Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 130, Number 12December 2022 Article DOIhttps://doi.org/10.1086/723278 Views: 643Total views on this site © 2022 The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.